Mapping framework conditions for societal participation of immigrants - a cluster analysis of medium-sized cities in Germany - Schade, Katrin (ERDKUNDE, 2023)
Immigrants, or people who are read as such, face unequal participation opportunities. This is mainly due to poor host country language skills, inexperience with and barriers within administrative processes. Especially in cities beyond metropolises, scepticism through inexperience regarding immigration reinforces inequality. Although immigration to smaller cities is increasing, studies regarding this remain scarce. The goal of this paper is to examine spatial-structural conditions of participation opportunities for immigrants in medium-sized cities (MSC) and thus develop a basis for further research to address the particular challenges for immigrants in MSC. Therefore, I question the spatial patterns and characteristics of immigrants’ participation opportunities in MSC. Cluster analysis and mapping methods are used to analyse data relevant to societal participation at the municipal level with reference to immigration. The data refer to MSC in Germany, a country that plays a significant role for immigration in Europe. Six clusters with different levels of participation opportunities emerge. One of the main results are the regional disparities between the former FRG (West Germany) and the former GDR (East Germany) expected under hypothesis 1. Almost all MSC in the former GDR can be assigned to the cluster with the greatest challenges for immigrants’ participation. At the same time, according to hypothesis 2, other regional differences can be identified, which are manifested by political-administrative boundaries, but also extend beyond them. Rural areas do not necessarily offer worse conditions for immigrants’ participation than dense regions. However, the mapping shows two participation ‘belts’ in the southwest between the large cities Frankfurt am Main and Stuttgart and in the central northwest between the Ruhr region and Hanover. The two belts contain a large number of strong MSC with good framework conditions for immigrant’s participation. Especially in the ‘arrival’ belt between Frankfurt am Main and Stuttgart it covers MSC of widely varying sizes. Hypothesis 3 illustrates how local peculiarities also in the former GDR allow contrary developments and show the importance of further research.